2007
DOI: 10.1002/adfm.200700063
|View full text |Cite
|
Sign up to set email alerts
|

Mesocellular Silica Foam as an Epoxy Polymer Reinforcing Agent

Abstract: A new type of mechanically improved rubbery epoxy composite is demonstrated based on the use of a mesocellular silica foam, denoted MSU‐F, as the reinforcement agent. The silica exhibits a surface area of 540 m2 g–1, a cell size of 26.5 nm (14.9 nm window size) and a pore volume of 2.2 cm3 g–1. Most notably, the silica foam particles readily disperse in the epoxy matrix without the need for an organic surface modifier or dispersing agent. Relative to the pristine polymer, the tensile modulus, strength, strain‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…It has been previously shown that hexagonal MCM-41 and cubic MCM-48 silica with framework pores sizes of only 3.0 nm act as conventional polymer reinforcing agents, similar to non-porous forms of silica of a comparable particle size. [27] Thus the pore size and pore volume offered by the particles are more important than the specific surface area for the formation of polymer mesocomposites with improved mechanical properties.…”
Section: Epoxy-msu-j Silica Mesocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that hexagonal MCM-41 and cubic MCM-48 silica with framework pores sizes of only 3.0 nm act as conventional polymer reinforcing agents, similar to non-porous forms of silica of a comparable particle size. [27] Thus the pore size and pore volume offered by the particles are more important than the specific surface area for the formation of polymer mesocomposites with improved mechanical properties.…”
Section: Epoxy-msu-j Silica Mesocompositesmentioning
confidence: 99%
“…Marginal improvements in the tensile properties also were observed for hexagonal MCM-41 silica filled polypropylene under supercritical CO 2 conditions. [24] Recently, low loadings of mesoporous silica with a three-dimensional wormhole framework structure (denoted MSU-J, 5.3 nm pore size) [25,26] or a mesocellular foam structure (denoted MSU-F, 26.6 nm pore size) [27] were reported as reinforcing agents for a thermoset rubbery epoxy polymer. Because the latter two forms of silica differ both in pore size as well as framework structure, it was not possible to distinguish J. Jiao et al / Reinforcement of a Rubbery Epoxy Polymer the contributions of pore size and pore structure in providing improved reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…tetraethylorthosilicate, TEOS) [9][10][11][12] or purely inorganic reagents (e.g., sodium silicate and colloidal silica) [12][13][14][15][16][17][18]. These mesostructured forms of silica show considerable promise as reinforcing agents for several engineering polymer systems at relatively low particle loadings due in part to the high surface area and favorable interfacial interactions between the polymer and the silica surface [19][20][21][22][23][24][25][26]. The unique pore structures provide enough intraparticle space for the polymer to impregnate the particles and form a unique composite structure.…”
Section: Introductionmentioning
confidence: 98%
“…Some of these composites exhibited improved tensile strength and tensile modulus as well as marginal improvements in toughness at specific loadings. In addition, the three-dimensional wormhole framework structure of MSU-J silica (5.3 nm pore size) [25] and the mesocellular foam structure of MSU-F silica (26.6 nm pore size) [26] have been shown to function as reinforcing and toughening agents in rubbery epoxy matrices at low loadings.…”
Section: Introductionmentioning
confidence: 98%
“…They have received much attention because of their ordered structure, high surface area and easiness for functionalization of the nanopores [12] . Mesoporous silica with many different pore sizes and structures such as hexagonal SBA-15, cubic MCM-48, hexagonal MCM-41, wormhole framework MSU-J, twodimensional, hexagonally ordered MSU-H, and mesocellular silica foam MSU-F silicas are synthesis and characterized by different groups [13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%